Pendampingan Traumatik Healing Pada Anak Usia Dini Pasca Terapi (Studi Kasus di Kelompok Bermain Mentari PKK Ngrogung Ngebel Ponorogo) - Diyan Asmawati Sya’ban; Tri Prasetyo Utomo; Adib Fuadi Nuriz (Social Science Academic, 2025)
Trauma healing is a process used to help someone recover from fear arising from past traumatic experiences. Through this process, a person can live again without being constantly haunted by painful memories from the past. The trauma healing assistance provided by the author to a student with the initials M, who attended the Mentari PKK Ngrogung Ngebel Ponorogo Playgroup, aimed to reduce or overcome the trauma felt by M after undergoing therapy, as well as to help M remember the trauma in a more positive way. The method used was Participatory Action Research (PAR). Participatory Action Research (PAR) is a research approach that places community participation at the center of the entire research process. The trauma healing assistance provided to M through three stages, namely restoring security, remembering and grieving, and connecting with daily life through play therapy and socializing with friends, showed effective results in overcoming the trauma experienced by M, as it brought significant changes or developments in M, especially in eliminating or reducing the trauma, anxiety, and fear experienced by M.